Colloidal characterization of CuO nanoparticles in biological and environmental media. Issue 6 (3rd April 2017) - Ortelli, Simona; Costa, Anna Luisa; Blosi, Magda; Brunelli, Andrea; Badetti, Elena; Bonetto, Alessandro; Hristozov, Danail; Marcomini, Antonio
Abstract : The relationships between the physicochemical properties of engineered nanomaterials (ENMs) and their adverse health and environmental effects are still unclear. Abstract : The relationships between the physicochemical properties of engineered nanomaterials (ENMs) and their adverse health and environmental effects are still unclear. In order to understand key nano-bio/eco interactions and to convert this knowledge into "Safety by Design" (Sby D) strategies, it is essential to study the colloidal properties of ENMs in nano(eco)toxicology-relevant media. In the frame of such a Sby D approach, this paper investigates the dispersion stability of copper oxide NPs surface-modified by means of four stabilizing agents, namely, [polyethylenimine (PEI), sodium ascorbate (ASC), sodium citrate (CIT), and polyvinylpyrrolidone (PVP)], which were used to achieve positive (PEI), negative (ASC, CIT), and neutral (PVP) surface charging of the NPs. The effects of these four stabilizers on the CuO NPs' physicochemical properties were investigated in different biological and environmental media by combining dynamic and electrophoretic light scattering (DLS and ELS), centrifugal separation analysis (CSA) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The results showed improved dispersion stability for CuO-CIT, CuO-ASC, and CuO-PEI in both Milli-Q and phosphate buffered saline (PBS) as compared to pristine CuO and CuO-PVP. The increased ionic strength of artificial fresh (AFW) and marine (AMW) waters strongly destabilized all the CuO NP suspensions, except for CuO-PEI dispersed in AFW. The presence of proteins and amino acids in the test media had a strong influence on the colloidal stability of all the dispersions. Characterization of colloidal properties and ion release rates in (eco)toxicological testing media will help to correlate some of these properties with (eco)toxicological responses, thus enabling prediction of the behavior of NPs in real environments.